The Urgency of the Tafhim Method from the Perspective of Muhammad Abduh: Its Relevance for Improving Students' Critical Skills - Qurratina, Noor Shania; Fahmi, Muhammad; Salik, Mohamad; Lutfiyah, Siti Khumairotul; Celine, Devi Rofidah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This research is motivated by problems related to learning methods that focus on memorization to hinder the development of student's critical thinking skills. Muhammad Abduh criticized it by proposing the concept of renewal related to learning methods of the times. This study aims to describe the tafhim method in learning Muhammad Abduh's perspective and analyze its relevance for improving students' critical thinking skills. This research is a type of library research, using descriptive-qualitative research methods with a philosophical-historical approach. The data collection technique uses documentation, listening, and note-taking techniques. The data analysis technique uses content analysis techniques. The result of the research is that Muhammad Abduh said that the memorization method must be equipped with a logical method and can increase understanding such as the tafhim method. This tafhim method consists of several learning models: concept understanding, question and answer, practice and experience, and discussion. The tafhim method proposed by Muhammad Abduh is relevant to the context of contemporary education. Through these methods, students can express their understanding in depth to improve their critical thinking skills